2008
DOI: 10.3945/ajcn.2008.26594
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the dietary requirement for vitamin D in healthy adults

Abstract: The range of vitamin D intakes required to ensure maintenance of wintertime vitamin D status [as defined by incremental cutoffs of serum 25(OH)D] in the vast majority (>97.5%) of 20-40-y-old adults, considering a variety of sun exposure preferences, is between 7.2 and 41.1 microg/d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
220
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(235 citation statements)
references
References 30 publications
14
220
1
Order By: Relevance
“…[20,21] One study suggested daily requirements of at least 1,600 IU D3 for optimal serum levels. [21] This dose was further analyzed in a randomized placebo control trial, where the mean serum 25(OH)D increased from 20.6 ng/ml to 33.7 ng/ml in the treatment group, but declined to 18.5 ng/ ml in the control group. [20] However, while encouraging, these findings suggest that even 1,600 IU D3 daily may fail to achieve the optimal serum threshold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20,21] One study suggested daily requirements of at least 1,600 IU D3 for optimal serum levels. [21] This dose was further analyzed in a randomized placebo control trial, where the mean serum 25(OH)D increased from 20.6 ng/ml to 33.7 ng/ml in the treatment group, but declined to 18.5 ng/ ml in the control group. [20] However, while encouraging, these findings suggest that even 1,600 IU D3 daily may fail to achieve the optimal serum threshold.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8,18,19] Numerous advantages of maintaining appropriate serum 25(OH)D continue to emerge, however, appropriate management remains controversial. [7,18,20,21] Multiple dosing protocols have been evaluated. [20,21] One study suggested daily requirements of at least 1,600 IU D3 for optimal serum levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both dietary supplementation and sunshine exposure are effective in preventing vitamin D deficiency (2,10). There is clear evidence that UV light exposure, consuming vitamin D-fortified food, and/or vitamin D supplementation has a positive impact on serum 25-hydroxyvitamin D (25OHD) concentrations, and adults can tolerate vitamin D at doses above the current dietary reference intake levels (11)(12)(13). Though both D2 and D3 have been used as supplements, D2 is less efficient compared with D3 for increasing serum 25OHD (10,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…
We have estimated the dietary requirement for vitamin D for a number of population sub-groups in winter (1)(2)(3) on the basis that the relative contribution of exposure of skin to UVB radiation from sunshine and diet to vitamin D status and vitamin D requirements are not fully understood. The North American Institute of Medicine took the same approach in establishing their recent Dietary Reference Intakes for vitamin D (4) .
…”
mentioning
confidence: 99%